A 40-GHz-bandwidth, 4-bit, time-interleaved A - Nathawad, L.Y (IEEE Journal of solid state circuits)
GaAs photoconductive switches have been integrated with two parallel 4-bit CMOS analog-to-digital (A/D) converter channels to demonstrate the time-interleaved sampling of wideband signals. The picosecond sampling aperture provided by low-temperature-grown-GaAs metal-semiconductor-metal switches, in combination with low-jitter short-pulse lasers, enables the optically-triggered sampling of electrical signals with tens of gigahertz bandwidth at low to medium resolution. A pair of parallel sampling paths, one for sampling and the second for feedthrough cancellation, generate a differential held signal that is quantized by a low-input capacitance, high-speed flash A/D converter. Dynamic offset averaging is employed to improve converter linearity. An experimental time-interleaved two-channel A/D converter provides about 3.5 effective bits of resolution for inputs up to 40 GHz when tested at an optically-triggered sampling rate of 160 MHz. The sampling rate was limited by the available optical source. Each A/D converter channel operates up to a 640-MHz conversion rate, dissipates 70 mW of power, and occupies an area of 150 μm × 450 μm in a 2.5-V, 0.25-μm CMOS technology.